The Use Of The Show And Tell Method On Student Communication Skills Class V Sd Private Surya Bakti - Septi Sazli, Namiroh (Berpusi Publishing, 2023)
This study aims to : (1) Know Skills communicate student class V of Surya Bakti Private Elementary School before use method learning Show and tell . (2) Knowing Skills communicate student class V of Surya Bakti Private Elementary School after use method learning Show And Tell . (3) Knowing influence method learning Show and Tell to Skills communicate student class V Surya Bakti Private Elementary School. This type of research is quantitative research experiment with the group design one group pretest-posttest design . The population of this study were all 28 students of class V at Surya Bakti Private Elementary School. The sampling technique used is saturated sampling where all members of the population are used as samples. Data collection techniques using observation sheets. Based on the research results : (1) Before use method learning Show And Tell that student 's average score Still low that is 66.57. (2) After use method learning Show and Tell student 's average score increase i.e. 89.07. (3) Based on this research, the results of calculating the hypothesis using the t test ( Paired Sample T Test ) at a significant level of 0.05 obtained a sig value. (2-tailed) is 0.000 ≤ 0.05, it can be said to be accepted and rejected. The results of the data analysis can be concluded that there is a very significant difference between the pretest and posttest thus there is an effect of using the Show method and Tell the communication skills of fifth grade students at Surya Bakti Private Elementary School for the 2022/2023 academic year.